Thiocarbamoylation of amine-containing compounds by tetramethylthiuram disulphide xiy(*). synthesis of 4-isothioxianato-2-(5-mercapto-i ,3,4oxadiazol-2-yl)-phenol. - Boi, Luu Van; Nguyen, Dong The (VNU Journal of Science: Natural Sciences and Technology; Vol 21 No 4, 2005)
Abstract